The Land Acquisition Compensation Process for Public Interest based on Law No. 2 of 2012 - Riduan, Amelia Marchela Putri; Winanti, Atik (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Law No. 2 of 2012 concerning Land Acquisition for Public Interest is carried out with the aim of providing land for development for the public interest by terminating the legal relationship between land rights holders and their land rights by providing appropriate compensation. And its implementing regulations are regulated in Presidential Regulation Number 71 of 2012. In the implementation of the Land Acquisition process, there are often obstacles in the process or become legal and social conflicts between land owners and institutions that need land. On this basis, the study aims to determine the process of providing land compensation that meets the principles of the Land Acquisition Law and this study is expected to be able to be used as a reference if similar problems occur. The method used in this study is Normative Jurisprudence, with a Statute Approach that is relevant to the Land Acquisition Law.The results of the study indicate that land acquisition for public interest as regulated in the Land Acquisition Law aims to create justice between the rights of land owners and the needs of national development. This process involves providing fair compensation, including physical and non-physical compensation, while taking into account the socio-economic balance of land owners. However, in its implementation, conflicts often arise related to the legitimacy of ownership and community resistance. This study emphasizes the importance of deliberation and dignified compensation mechanisms to maintain socio-economic stability. The conclusion of the research isCompensation is carried out transparently and through deliberation, taking into account the balance between landowner rights and development needs. The form of compensation includes physical and non-physical, aiming to maintain the socio-economic stability of landowners while supporting national development and protecting the rights of all parties in need.